THE RELEVANCE BETWEEN COMMUNITY KNOWLEDGE AND PERCEPTION TOWARDS SANITATION FACILITY USAGE BEHAVIOR IN CISANGGARUNG VILLLAGE, CIMENYAN DISTRICT, BANDUNG REGENCY, WEST JAVA - Pramita Nurfitriani, Ashfia
Despite advancements in sanitation infrastructure, many communities in West Java still grapple with inadequate sanitation practices. This study investigates factors influencing the utilization of sanitation facilities, specifically defecation behavior in MCKs (community toilet blocks) and septic tank management. A sample of 105 individuals from Cisanggarung Village was surveyed, employing the RANAS (risk, attitude, norm, ability, and self-regulation). The RANAS is used as the research framework and the independent variables studied against the dependent variable of behavior. The results of the study indicate that the level of knowledge and perception of the community regarding defecation behavior in the MCK is high, but low for septic tank handling behavior. Data processing with multiple linear regression analysis showed that there was a significant statistical relationship between the RANAS and defecation behavior in the MCK (r = 0.756, R² = 0.572, p < 0.001) as well as RANAS and behavior towards septic tanks (r = 0.568, R² = 0.322, p < 0.001). Norm and ability factors significantly contributed to defecation behavior in the MCK, while the norm factor was the main contributor to septic tank handling behavior.